PREVALENCE AND IDENTIFICATION OF ECTOPARASITES IN KINTAMANI BALI DOG IN BALI - Murti, Ni Wayan Nur Sidi; Oka, Ida Bagus Made; Dwinata, I Made (Buletin Veteriner Udayana, 2023)
Ectoparasites are parasites that live parasitically on the outside of the host's body or tunnels in the skin that are still in contact with the external environment. Impacts caused by ectoparasite infestations in dogs include decreased body weight, decreased production, hair loss, irritation, anemia and even death. The purpose of this study was to determine the prevalence of infestation and identification of ectoparasites that infest the Anjing Kintamani Bali (AKB). The AKB samples used were 100 individuals. The Anjing Kintamani Bali selected as the sample tested positive if ectoparasites were found in the dog. Identification of ectoparasites based on morphology. The data obtained were analyzed by Chi-square test. The results showed that the prevalence of ectoparasites in AKB in Bali was 56%. The types of ectoparasites that infest include: Riphicephalus sanguinus, Ctenocephalides felis, Heterodoxus spiniger and Trichodectes canis . Chi-square test found that maintenance methods were associated with the prevalence of ectoparasite infestations in AKB in Bali, while age and sex were not correlated. Maintenance of the Anjing Kintamani Bali in Bali, you should pay more attention to animal health. Regular bathing of animals is highly recommended to control ectoparasite infestations, besides that the owner can comb the animals regularly. Sanitation of cages for animals in cages is very important to pay attention to, besides that, it is better for animals that have been severely infested to be taken to the nearest veterinarian.